Analysis of Business Actors’ Satisfaction with BPOM’s One Stop Service in the Registration of Herbal Medicines, Health Supplements, and Cosmetics - Mohamad Kashuri (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
The One Stop Service provided by the Indonesian Food and Drug Authority is designed to streamline the registration procedures for herbal medicines, cosmetics, and health supplements. This service is essential for improving efficiency, accessibility, and user satisfaction; however, empirical evaluations of user satisfaction remain limited. Previous studies highlight that service quality, communication, and responsiveness are key factors influencing satisfaction, but specific research on BPOM’s OSS is scarce. This study aims to evaluate user satisfaction levels, identify key determining factors, and provide recommendations for improving the service. A quantitative approach was employed, collecting data through questionnaires from participants who engaged in the service, both offline and online. The results indicate that most respondents were satisfied, particularly with processing time, ease of access, and staff responsiveness. However, areas requiring improvement include the development of digital features, more equitable service distribution, and enhanced transparency in communication. This study offers novelty by emphasizing the importance of a holistic approach that incorporates dimensions of communication, privacy, and inclusivity.